(untitled) (Huellas, 2025)
Along the banks of the Colorado River, there are populations highly dependent on water resources, as it is an arid region. Since the last century, the uses of this allochthonous river in Northern Patagonia have multiplied. However, La Pampa’s environmental policing power is insufficient to control industrial, sewage, and oil spills, due to the competence scope of the interjurisdictional committee. The research, conducted between 2022 and 2024, aimed to identify sources of contamination and gaps in monitoring and control through physical-chemical and bacteriological water analyses and studies of benthic ostracod communities (bioindicators) in sediments found in riverside locations. Participant observation also included surveys of mini-dumps, waste collection centers, and urban drainage areas, in addition to interviews with key informants and the verification of official information. The importance of the study lies in assessing the effects of pollution in Rincón de los Sauces and its worsening downstream, using a holistic and multidimensional methodological approach. This approach identified problems that challenge the actions of the State, which is the ultimately responsible for ensuring access to drinking water, working on risk management and providing public information for the protection of water resources.